Tuning in to consumers: Tailoring African rice value chains to urban markets - Rizzotto, A.C.; Demont, M. (2011)
In response to the 2008 food crisis, Senegal developed an ambitious food self-sufficiency programme which aims to entirely cover national rice consumption needs with local rice by 2015, mainly through massive investments in existing and new rice perimeters in the Senegal River Valley (SRV). It has yet to be seen, however, how the projected rice production boom will reach urban markets, where the product is often unknown or misconstrued. Therefore, in this article, we highlight the role of generic promotion programmes in tailoring emerging quality SRV rice value chains to urban consumer standards.